Evaluation of procedures used to determine the population and sample in postgraduate research works - Mucha Hospinal, Luis Florencio (2021)
Objective. To evaluate the procedures used to determine the population and the sample in research works carried out to obtain a master's degree at the Universidad César Vallejo, Huancayo. Methods. The research was of basic type, descriptive level and simple descriptive design. The sample consisted of 202 research papers with a quantitative approach that were analyzed with the evaluation form of population and sample criteria designed for the study. Results. 100% of the studies used non-probabilistic sampling, did not present a theoretical population, did not consider inclusion and exclusion criteria, and considered the sample size inadequately. The 97.5 % of the studies with quantitative variables did not specify the type and technique of sampling and 42.5 % of the studies with qualitative variables did so inadequately. Conclusions. The procedures used to determine the population and sample in the unit of analysis were inadequate, showing weakness in the application of sampling theory.